Co‐gasification of woody biomass and sewage sludge in a fixed‐bed downdraft gasifier. Issue 8 (20th April 2015) - Ong, Zhehan; Cheng, Yongpan; Maneerung, Thawatchai; Yao, Zhiyi; Tong, Yen Wah; Wang, Chi‐Hwa; Dai, Yanjun
<x xml:space="preserve">Abstract</x> Experimental and numerical studies of cogasification of woody biomass and sewage sludge have been carried out. The gasification experiments were performed in a fixed‐bed downdraft gasifier and the experimental results show that 20 wt % dried sewage sludge in the feedstock was effectively gasified to generate producer gas comprising over 30 vol % of syngas with an average lower heating value of 4.5 MJ/Nm3. Further increasing sewage sludge content to 33 wt % leads to the blockage of gasifier, which is resulted from the formation of agglomerated ash. The numerical models were then developed to simulate the reactions taking place in four different zones of the gasifier (i.e., drying, pyrolysis, combustion, and reduction zones) and to predict the producer gas composition and cold gas efficiency. The deviation between the numerical and experimental results obtained was lower than 10%. © 2015 American Institute of Chemical Engineers AIChE J, 61: 2508–2521, 2015